Innovative tools to predict and improve seed physiological quality: case studies in tomato and soybean - Petronilio, Ana Carolina Picinini [UNESP] (2024)
The seed quality is made up of physical, sanitary, genetic, and physiological attributes. Seed physiological quality refers to factors that allow rapid and uniform germination and emergence under broad climatic conditions, which ensures vigorous initial plant establishment and produces an increased yield. This research sought to elucidate how the physiological quality of seeds can be predicted and improved. To this end, this research used soybean and tomato species as models. 1 – the physiological quality of soybean seeds produced under water and heat stress during the maturation phase was determined, and seed multispectral images were acquired. Machine learning models associated with multispectral imaging technology were developed to verify the possibility of separating seed groups autonomously. The quality of stressed seeds was lower compared to non-stressed ones. The multispectral images produced markers that made it possible the segmentation between seed groups. The ML models showed high performance in recognizing stressed seeds. This work opens up the possibility of using this technology as a results manager, as it provides information about the environment of seed production and its consequences on the physiological quality of the seeds. 2 – we performed soybean genetic transformations for further study of the molecular factors involved in seed chlorophyll degrading/retention. For this, the GmABI5 gene was overexpressed and silenced (RNAi) using the glycinin promoter in a hygromycin-resistant expression cassette. Somatic embryos were induced from the cotyledons of immature seeds and when they reached the globular stage they were transformed via bioballistics. Transformed embryos were selected for resistance to hygromycin. The presence of the expression cassette in the resistant embryos was confirmed via PCR and they were regenerated into seedlings. This work will allow the functional study of the ABI5 gene and also the investigation into the possibility of reproducing a genotype tolerant to chlorophyll retention in soybean seeds. 3 – we performed gene expression studies in tomato seeds during osmo-priming to investigate mechanisms involved in the reduction of longevity. For this, we collected a total of seven samples: four samples during the 60 hours of priming, one control group (without priming), one sample after post-priming drying, and one after post-priming thermal shock and drying. We investigated transcripts associated with stress response. The seed vigor and longevity after treatment were also determined. Primed seeds had their longevity impaired compared to unprimed ones. Genes from the heat-shock protein family were down-regulated during the priming process. This research brings new insights into the mechanisms involved in the reduction of longevity of primed seeds and allows the use of these transcripts to monitor longevity in primed tomato seeds.